Broad-line Type Ic supernova SN 2014ad. Issue 2 (31st January 2018) - Sahu, D K; Anupama, G C; Chakradhari, N K; Srivastav, S; Tanaka, Masaomi; Maeda, Keiichi; Nomoto, Ken'ichi
Abstract: We present optical and ultraviolet photometry and low-resolution optical spectroscopy of the broad-line Type Ic supernova SN 2014ad in the galaxy PGC 37625 (Mrk 1309), covering the evolution of the supernova during −5 to +87 d with respect to the date of maximum in the B band. A late-phase spectrum obtained at +340 d is also presented. With an absolute V -band magnitude at peak of MV = −18.86 ± 0.23 mag, SN 2014ad is fainter than supernovae associated with gamma ray bursts (GRBs), and brighter than most of the normal and broad-line Type Ic supernovae without an associated GRB. The spectral evolution indicates that the expansion velocity of the ejecta, as measured using the Si ii line, is as high as ∼33 500 km s −1 around maximum, while during the post-maximum phase it settles at ∼15 000 km s −1 . The expansion velocity of SN 2014ad is higher than that of all other well-observed broad-line Type Ic supernovae except for the GRB-associated SN 2010bh. The explosion parameters, determined by applying Arnett's analytical light-curve model to the observed bolometric light-curve, indicate that it was an energetic explosion with a kinetic energy of ∼(1 ± 0.3) × 10 52 erg and a total ejected mass of ∼(3.3 ± 0.8) M⊙, and that ∼0.24 M⊙ of 56 Ni was synthesized in the explosion. The metallicity of the host galaxy near the supernova region is estimated to be ∼0.5 Z⊙ .